(untitled) (Revista Lusófona de Educação, 2025)
The paper presents a study carried out as part of the research project LC4Inclusion - On the road to schools as communities for inclusion. It focuses on teachers’ attitudes towards inclusive education and diversity in groups of schools involved in the Portuguese Network of Learning Communities INCLUD-ED, which the Directorate-General for Education promoted at national level. 154 responses to a questionnaire, inspired by the Index for Inclusion and previously validated in Portuguese schools, were analysed. The results are in line with other studies and point to an overall positive attitude towards the three dimensions analysed in the factor analysis: Diversity and educational inclusion; Inclusive cultures; Inclusive classroom practices, as well as positive and significant correlations between these dimensions, revealing their interdependence. The results also revealed that attending training in inclusive education, self-perceived knowledge about diversity and inclusion, positive previous experiences with students with specific needs and the lower levels of education at which teachers teach are significantly associated to more positive attitudes towards inclusive education. Keywords: Teachers’ attitudes; Diversity; Inclusive cultures; Inclusive policies; Inclusive practices.